PSYCHOLOGICAL PECULIARITIES OF CONFLICT BEHAVIOR IN YOUNG ADULT AGE - Andrieieva, Yaroslava; Lytovchenko, Nina (PSYCHOLOGICAL JOURNAL, 2019)
The paper deals with theoretical review and empirical study of the peculiarities of conflict behavior in young adult age during their professional training. The process of professional becoming and intrapsychic controversies, arising during professional becoming and critical periods of the given stage are analyzed. Taking the theoretical review of psychological literature as the basis of our study, we can define the process of professional becoming as “the formation of professional orientation, competency, integration of socially meaningful and professionally important qualities, readiness to professional advancement, search for optimal means of qualitative and creative professional activity in accordance with person’s individual-psychological qualities” (Zeer Ye.) Critical stages of professional training can be divided into two groups: crisis of learning-professional orientation on the stage of optation and the crisis of the professional choice on the stage of professional training. The first crisis has the naive professional choice, situational choice of the higher educational institution, lack of individual-psychological features consideration as its’ agents. The second crisis is characterized by dissatisfaction with one’s professional education, changes in social-economical life conditions, changes in personality’s leading activity (Zeer Ye., Symanyuk Ye., Shchotka O.). The peculiarities of the conflict behavior of the students’ youth under conditions of learning activities are the subject of the empirical study. According to the hypothesis the peculiar features of the current teaching process’ organization, and especially ECTS system can be an external agent resulting in interpersonal conflict in academic groups and the choice of the conflict behavior strategy. Comparative analysis of data taken in the experimental and the control group gave the grounds to analyze behavioral strategy, its impact on the personality and group interactions. The results of the empirical study proved that ECTS system of training organization does not determine conflicts in academic groups, but rather demonstrates the wast specter of problems pertain to the process of organizing learning and training students’ with mainly external learning motivation activity. Our evidence suggests that students enrolled in the university mainly have conflicts through rating and scholarships, and these conflicts can lead to negative consequences.